The EOLES project Engineering labs anywhere - Fidalgo, André (2019)
The EOLES (Electronics and Optics e-Learning for Embedded Systems) project is a 3-year joint project involving 15 institutions, four from Europe and eleven from the North African countries of Algeria, Morocco, and Tunisia, whose aim is to create a 3rd year Bachelor degree in Electronics and Optics for Embedded Systems. The project started in October 2012 and is scheduled to end in October 2015.